STRATEGI GURU DALAM MENGATASI KECEMASAN MATEMATIKA (MATH ANXIETY) PADA SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstrak This study aims to analyze teacher strategies in reducing mathematics anxiety among elementary school students through a qualitative literature-based approach. Mathematics anxiety, characterized by fear, tension, and avoidance when dealing with mathematical tasks, has been shown to negatively affect students’ conceptual understanding, working memory, motivation, and overall academic performance. Recent studies indicate that a high proportion of elementary students in Indonesia experience moderate to high levels of math anxiety, which are influenced by low self-efficacy, negative learning experiences, teacher-centered instruction, and classroom environments that emphasize speed and correctness. This study employed a qualitative literature review by examining national and international research articles published between 2015 and 2025 that discuss the causes of math anxiety and teacher strategies for overcoming it. The analysis reveals three major groups of effective strategies: pedagogical strategies, such as contextual learning, the use of manipulatives, and game-based instruction; psychological strategies, including positive reinforcement, supportive communication, and the development of a growth mindset; and classroom management strategies, such as cooperative learning, Think Pair Share, and creating error-friendly learning environments. The findings conclude that teacher practices combining engaging pedagogy, emotional support, and positive classroom climate significantly contribute to reducing students’ math anxiety and improving their confidence in learning mathematics. Keywords: math anxiety, teacher strategies, elementary mathematics learning